2012
DOI: 10.1007/s00384-012-1410-1
|View full text |Cite
|
Sign up to set email alerts
|

Has laparoscopic colorectal surgery become more cost-effective over time?

Abstract: From the current trends, it is projected that the results of future economic evaluations will unequivocally show that laparoscopic surgery is cheaper than open surgery. The initial higher costs of laparoscopic surgery training may be worth the savings made in the long term if it is practised in settings where postoperative care is expensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This study did not include imaging costs, prescribed medication costs, outpatient costs, or community costs. Despite not having included these, similar values to previous studies were observed [10-12, 14-17]. Early laparoscopy cost-effectiveness studies, reported varying results comparing the cost of laparoscopic to open colorectal surgery [15, 17].…”
Section: Discussion/conclusionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study did not include imaging costs, prescribed medication costs, outpatient costs, or community costs. Despite not having included these, similar values to previous studies were observed [10-12, 14-17]. Early laparoscopy cost-effectiveness studies, reported varying results comparing the cost of laparoscopic to open colorectal surgery [15, 17].…”
Section: Discussion/conclusionsupporting
confidence: 76%
“…Higher operating room costs were due to more expensive equipment and longer operation duration due to the learning curve of the new laparoscopic approach [16]. In more recent studies, cost-benefits for laparoscopic surgery were realized with shorter LOS and better postoperative outcomes [10-12, 14]. Keller et al [12] reported a reduction of 22% in hospital costs in favor of laparoscopic surgery (OR 0.78, C.I.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It must also be considered that the robotic surgery market has been driven by one main provider during the last two decades, and that the arrival of competitors should allow for costs to be diminished and favour the evolution of platforms towards incremental versatility. In an analogous scenario, and non-surprisingly in hindsight, Aly et al [ 8 ] showed that laparoscopic colorectal surgery is becoming more cost-effective over time. In this systematic review, the authors showed that the cost-difference percentage between both approaches is decreasing over time (R-value = − 0.44; P = 0.046), projecting that the results of future economic evaluations would unequivocally show that laparoscopic surgery is cheaper than open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant difference in the index hospitalization costs between laparoscopic and open cases ($24 196 vs $31 601), which is in agreement with the trend seen in a recent systemic review. 9 In addition, in both the initial 3 months and the first year after surgery, patients who underwent laparoscopic procedures were significantly more likely to require fewer days of health care utilization and spend less on their overall health care and drug expenses. These results likely reflect the well-documented benefits of laparoscopy, which include faster recovery, less pain, and fewer complications.…”
Section: Discussionmentioning
confidence: 99%
“…2 This increase in up-front costs, however, is offset by decreases in length of stay, complications, readmissions, and mortality, each of which can carry significant financial consequences. 8 In addition, a recent systemic review 9 showed that, as experience with laparoscopy has increased, there has been a trend toward overall improved cost-effectiveness compared with open surgery. While these short-term outcomes are significant, there has been little research into the long-term effects of laparoscopy on health care resource utilization beyond the immediate postoperative period.…”
mentioning
confidence: 99%